A STUDY OF INSTRUCTORS’ DECISION MAKING STYLES IN GRADUATE SCHOOL OF EDUCATION AND GRADUATE SCHOOL OF PSYCHOLOGY AT ASSUMPTION UNIVERSITY OF THAILAND - cekka, Panya; Ye, Yan (Scholar: Human Sciences, 2015)
This study intended to describe the demographic data and decision making styles of instructors in the Graduate School of Education and the Graduate School Psychology at Assumption University of Thailand. Ten instructors from Graduate School of Education and four instructors from the Graduate School of Psychology were used in this case study. The study was primarily based on three decision making styles: autocratic style, consultative style and group style. Questionnaires using Likert scale included two parts: demographics and decision making styles. The collected questionnaires were computed by the descriptive statistics including frequency, percentage and mean. This study found which decision making style the instructors most practice when they attempted to make a decision concerning the issues they confronted in faculties. The instructors’ demographic results showed that in both schools, male and female instructors are same in number, the majority instructors were Non-Thai nationalities, they were over 50 years-old, with more than 20 years’ work experiences as well, and all instructors had got Ph. D. Meanwhile, the Group (shared) decision making style was found as the most preferred decision making style in the study. Discussion and recommendations on how to provide instructors effective decision making style for faculties were provided in the last part of the study.